Fused Filament Fabrication 3D Printing Parameters Affecting the Translucency of Polylactic Acid Parts - Vochozka, Vladimír; Černý, Pavel; Šramhauser, Karel; Špalek, František; Kříž, Pavel; Čech, Jiří; Zoubek, Tomáš; Bartoš, Petr; Kresan, Jan; Stehlík, Radim (Polymers, 2024)
The effect of 3D printing parameters by Fused Filament Fabrication (FFF) on the translucency of polylactic acid (PLA) parts was investigated. Six different printing parameters were studied: object orientation, layer height, nozzle temperature, fan speed, extrusion multiplier, and printing speed. The commercially available Plasty Mladeč PLA filament and the Original Prusa MK4 3D printer were used for the experiments. The translucency of the printed samples of 50 × 25 × 1 mm dimensions was measured using a luxmeter in an integrating sphere. A total of 32 sample combinations were created. Each sample was printed ten times. The results show that all investigated parameters significantly affect the optical properties of PLA parts. The best measured translucency values were obtained when printing in portrait mode, with a layer height of 0.30 mm, nozzle temperature of 240 °C, fan speed of 100%, 0.75 set extrusion multiplier, and a speed of 40 mm/s. ANOVA was used to statistically evaluate the effect of each parameter on translucency, and statistically significant differences were found between different combinations of parameters (p < 0.05). Scanning Electron Microscope (SEM) analysis provided detailed images of the surface structure of the printed samples, allowing for a better discussion of the microscopic properties affecting the translucency. The best print setting has an efficiency of 88% compared to the default setting of 65%. The ability of visible light to pass through the print (translucency) improved by 23%.
Keywords: layer height; FFF; translucence; nozzle temperature; fan speed; slicer; polylactic acid; HSD test; ANOVA; integrating sphere; extrusion multiplier; luxmeter